Cusp overlap technique for transcatheter self-expanding aortic valve implantation - Sacha, Jerzy; Krawczyk, Krzysztof; Gwóźdź, Witold; Bugajski, Jarosław; Darmetko, Mariusz; Gierlotka, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Transcatheter aortic valve implantation (TAVI) may cause atrioventricular conduction disturbances and, consequently, the necessity for permanent pacemaker implantation (PPI). This is because the His bundle surfaces at the basal part of the membranous septum (in the neighbourhood of the non-coronary cusp) and implant depth greater than the length of the membranous septum may interfere with the conduction system [1]. To mitigate this risk, the valve should be implanted at a high position to minimize the contact of the valve frame with the base of membranous septum. During TAVI, the valve is usually positioned in a coplanar fluoroscopic projection with 3 cusps view, but for a self-expanding valve, like the Evolut R (Medtronic, Minneapolis, Minnesota), such a view does not ensure a high implantation. However, a recently proposed technique based on a cusp overlap allows valve implantation at a very high position and significantly reduces the risk of PPI [2, 3].